GhROP6 GTPase modulates auxin accumulation in cotton fibers by regulating cell-specific GhPIN3a localization. (18th October 2022) - Xi, Jing; Zeng, Jianyan; Fu, Xingxian; Zhang, Liuqin; Li, Gailing; Li, Baoxia; Yan, Xingying; Chu, Qingqing; Xiao, Yuehua; Pei, Yan; Zhang, Mi
Abstract: PIN-FORMED- (PIN) mediated polar auxin transport plays a predominant role in most auxin-triggered organogenesis in plants. Global control of PIN polarity at the plasma membrane contributes to the essential establishment of auxin maxima in most multicellular tissues. However, establishment of auxin maxima in single cells is poorly understood. Cotton fibers, derived from ovule epidermal cells by auxin-triggered cell protrusion, provide an ideal model to explore the underlying mechanism. Here, we report that cell-specific degradation of GhPIN3a, which guides the establishment of the auxin gradient in cotton ovule epidermal cells, is associated with the preferential expression of GhROP6 GTPase in fiber cells. In turn, GhROP6 reduces GhPIN3a abundance at the plasma membrane and facilitates intracellular proteolysis of GhPIN3a. Overexpression and activation of GhROP6 promote cell elongation, resulting in a substantial improvement in cotton fiber length. Abstract : Cell-specific protein degradation of GhPIN3a is responsible for establishing auxin maxima in discrete single cotton fibers, where preferential activation of GhROP6 signaling enhances this process through impairing GhPIN3a plasma membrane abundance.